Evaluation of microsatellite instability patterns in mismatch repair deficiency: a retrospective analysis of 285 endometrial cancers - Wang, Cheng; Feng, Min; Kou, Yuling; Kuang, Wei; Wang, Wei; Liang, Dongni (Frontiers in Immunology, 2025)
ObjectiveIn this study, we systematically compared the microsatellite shift patterns detected by PCR-based microsatellite instability analysis (PCR-MSI) in mismatch repair (MMR)-deficient ECs and analyzed the clinicopathological features associated with minimal versus major shifts.MethodWe evaluated the microsatellite shift patterns using five NCI-recommended loci in 285 MMR-deficient ECs identified through immunohistochemistry (IHC). A minimal shift was defined as a one-to-three nucleotide repeat shift observed at least at one locus. Then, clinicopathological characteristics were analyzed for two distinct groups: the minimal shift group and the major shift group. Finally, further analysis of MMR/MSI discordant cases was performed through MLH1 promoter methylation detection and MMR gene germline mutation detection.ResultOf the 285 MMR-deficiency ECs, 169 (59.3%) had combined loss of MLH1 and PMS2, 54 (18.9%) had combined loss of MSH2 and MSH6, 39 (13.7%) had isolated loss of MSH6 and 23 (8.1%) had isolated loss of PMS2 by IHC. The rate of inconsistency between MMR-IHC and PCR-MSI was 12.3% (35/285). However, based on the minimal shifting criteria, 13 cases with MSI-L were reassessed as MSI-H because of the occurrence of minimal microsatellite shifts, and the inconsistency rate between MMR-IHC and MSI-PCR decreased to 7.7% (22/285). Additionally, discordant cases showed a higher frequency (91%, 20/22 cases) of minimal shift involving the mononucleotide locus. Among the 7 MLH1/PMS2-deficient cases, 3 were successfully detected and showed MLH1 promoter methylation. A total of 13 of 22 patients were successfully completed MMR gene germline testing, 11 cases had germline mutations in MSH6 and 3 cases harbored frameshift deletions (p.F1088Lfs*). Overall, the frequency of minimal shift was 100% (39/39) at isolated loss of MSH6, 85.8% (145/169) at the loss of MLH1 and PMS2, 66.7% (36/54) at the loss of MSH2 and MSH6, and 47.9% (11/23) at the isolated loss of PMS2, respectively. There is no correlation between minimal shift group or major shift group and clinicopathological features.ConclusionMMR-deficient ECs exhibit a high frequency of minimal microsatellite shifts, particularly in cases with isolated loss of MSH6. The combination of MMR-IHC and MSI-PCR assays could enhance the accuracy of MSI detection, thereby facilitating more precise treatment strategies of ECs.